VS-5584, a Novel PI3K-mTOR Dual Inhibitor, Inhibits Melanoma Cell Growth In Vitro and In Vivo - Shao, Zheren (Public Library of Science, 2015)

(untitled) (PLoS One)
Melanomas cause over 76% of skin cancer deaths annually. Phosphatidylinositol 3-kinase (PI3K)-AKT-mammalian target of rapamycin (mTOR) signaling pathway is important for melanoma initiation and progression. In the current study, we evaluated the potential anti-melanoma effect of VS-5584, a novel and highly potent PI3K-mTOR dual inhibitor. We demonstrated that VS-5584 potently inhibited survival and proliferation of established (A375, A-2058 and SK-MEL-3 lines) and primary human melanoma cells, but was non-cytotoxic to non-cancerous human skin keratinocytes and B10BR murine melanocytes. At the meantime, VS-5584 induced caspase-dependent apoptotic death in melanoma cells, and its cytotoxicity was alleviated by the caspase inhibitors. At the molecular level, VS-5584 blocked AKT-mTOR activation and downregulated cyclin D1 expression in melanoma cells, while the expressions of Bcl-xL and Bcl-2 were not affected by VS-5584 treatment. On the other hand, a BH-3 mimetic Bcl-xL/Bcl-2 inhibitor ABT-737, as well as siRNA-mediated knockdown of Bcl-xL or Bcl-2, enhanced the activity of VS-5584 in melanoma cells. In vivo, oral administration of VS-5584 suppressed A375 melanoma xenograft growth in nude mice, and its activity was further enhanced by co-administration of ABT-737. These results provide the rationale for the clinical assessment of VS-5584 in melanoma patients and development of ABT-737 and other Bcl-xL/Bcl-2 inhibitors as the possible adjuvants.